Use of SWOT analysis to select feasible businesses as the mainstay business of BUMDes and MSMEs - Marselina, Marselina; Prasetyo, Tri Joko; Ciptawaty, Ukhti; Aida, Neli; Suparta, I Wayan (Research and Social Study Institute, 2024)
COVID-19 pandemic, which lasted from 2020 to 2022, has affected the global economy. Activity restrictions had hampered the progress of various business sectors. As a result, there was a decline in economic growth globally. There was even an economic contraction of -13.7% in 2020 and many businesses experienced either setbacks or bankruptcies. Indonesia’s government made various recovery efforts, such as business assistance through village-owned enterprises (BUMDes) activities and capital assistance for MSMEs in the form of people’s business credit (Kredit Usaha Rakyat/KUR). Various trainings and assistance were conducted, but these activities focused more on reporting and administration of funds. The establishment of BUMDes mainly aims to improve the villages’ economy. The selection of BUMDes' mainstay business is highly important to realize the smooth running of the business chosen. For this reason, it is necessary to conduct training on how to select of the mainstay business and calculate the feasibility of the business chosen to be developed so that BUMDes and MSME actors can manage and develop their business properly. The selection can use SWOT analysis, namely by analyzing the strengths, weaknesses, opportunities, and threats of the potential business options. In this community services activity, BUMDes and MSME training was held in Bogorejo Village, Pesawaran Regency, Lampung Province. The results of SWOT analysis reveal that the feasible business options are digital financial services (BRI-Link), agricultural trading (waserda), and waste collection and waste bank. Waserda business aims to help market the local community's products. Waste management business economically generates small profits, but has long-term positive effects, both environmentally and socially. Meanwhile, tourism park and savings and loan are considered not feasible in the long-term, as these businesses are susceptible to bottlenecks and large losses so that they must be managed very carefully.